2000
DOI: 10.4049/jimmunol.164.12.6287
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Up-Regulated Protein 1 Mediates Oxidative Stress Via Suppressing the Thioredoxin Function

Abstract: As a result of identifying the regulatory proteins of thioredoxin (TRX), a murine homologue for human vitamin D3 up-regulated protein 1 (VDUP1) was identified from a yeast two-hybrid screen. Cotransfection into 293 cells and precipitation assays confirmed that mouse VDUP1 (mVDUP1) bound to TRX, but it failed to bind to a Cys32 and Cys35 mutant TRX, suggesting the redox-active site is critical for binding. mVDUP1 was ubiquitously expressed in various tissues and located in the cytoplasm. Biochemical analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
399
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(434 citation statements)
references
References 50 publications
22
399
2
2
Order By: Relevance
“…We believe that this is due to the fact that most of the previous studies assessed only TBP-2 mRNA, not protein. Studies showed increased levels of TBP-2 mRNA after oxidative stress 37 or glucose loading, 38 and a decrease in the mRNA level in several human [39][40][41] and animal tumors. 42 Re-evaluation of these experiments may be necessary because of the inconsistency between the mRNA and protein levels of TBP-2.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this is due to the fact that most of the previous studies assessed only TBP-2 mRNA, not protein. Studies showed increased levels of TBP-2 mRNA after oxidative stress 37 or glucose loading, 38 and a decrease in the mRNA level in several human [39][40][41] and animal tumors. 42 Re-evaluation of these experiments may be necessary because of the inconsistency between the mRNA and protein levels of TBP-2.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Thioredoxin-interacting protein (TXNIP) is a negative regulator of thioredoxin function, inhibiting its reducing capacity 13 and promoting cellular oxidative stress. TXNIP expression is ubiquitous and is induced by a variety of cellular stresses, including high intracellular glucose.…”
mentioning
confidence: 99%
“…Inability of the overexpressed redox-inactive Trx in suppressing PPAR␣ activity ( Figure 6, A and B) suggests a critical role for the redox-active site (Cys32 and Cys35) of Trx. This conclusion was further supported by increased suppression of the binding activity of PPAR␣ to PPRE in vitro in the presence of TrxR, the primary enzyme catalyzing Trx reduction (Figure 8), and an increased inhibition of PPAR␣ transcriptional activity in the cells having Txnip, the endogenous redox inhibitor of Trx (Junn et al, 2000), knocked down by Txnip siRNA. Because TrxR and Txnip have been reported to be involved in promoting and blocking nuclear localization of Trx, respectively (Karimpour et al, 2002;Schulze et al, 2002), the observed enhanced inhibition PPAR␣ activity by TrxR and Txnip siRNA may be also due to an alteration of subcellular distribution of Trx.…”
Section: Discussionmentioning
confidence: 56%
“…It was found that the resulted PPAR␣ activity increased as goldthioglucose concentration increased ( Figure 6C). Furthermore, it was also investigated if Txnip, the negative modulator of Trx (Junn et al, 2000), affects the Trx-regulated PPAR␣ activity. Txnip siRNA was used to knockdown the endogenous Txnip.…”
mentioning
confidence: 99%